Way out in the desert - Marsh, T. J., 1960-; Ward, Jennifer, 1963-; Spengler, Kenneth (Flagstaff, AZ : Rising Moon, 1998)
A counting book in rhyme presents various desert animals and their children, from a mother horned toad and her little toadie one to a mom tarantula and her little spiders ten. Numerals are hidden in each illustration.
Keywords: Desert animals -- Fiction; Animals -- Infancy -- Fiction; Counting; Picture puzzles; Stories in rhyme